Syzygium aromaticum (L.) Merr. & L.M. Perry Extract Restores Immune Homeostasis and Accelerates Healing in MRSA-Infected Wounds: A Mechanistic In Vivo Study via Downregulation of TNF-α, CRP, and IL-10 - Rizal Arief Muttaqien; Eriawan Agung Nugroho; Gina Yunita Joice Sitorus (HM Publisher, 2026)
Background: The rise of Methicillin-Resistant Staphylococcus aureus (MRSA) in surgical site infections necessitates the development of non-resistant therapeutic adjuvants. Syzygium aromaticum (Clove) possesses known antimicrobial properties, yet its specific immunomodulatory effects on the MRSA-induced cytokine storm and wound chronicity remain under-characterized. This study investigated the efficacy of a standardized ethanolic extract of S. aromaticum flower buds in modulating the inflammatory milieu and accelerating wound repair. Methods: A true experimental study was conducted using 30 male Wistar rats with MRSA-infected dorsal excision wounds. Subjects were randomized into six groups (n=5): Normal Control (K1), Negative Control (MRSA+Vehicle, K2), Positive Control (MRSA+Vancomycin, K3), and treatment groups receiving 25 mg (P1), 50 mg (P2), and 100 mg/200g BW (P3) of extract orally for 10 days. The extract was characterized via HPLC. Serum TNF-α, CRP, and IL-10 were quantified by ELISA. Secondary outcomes included bacterial load reduction and macroscopic wound contraction rates. Results: HPLC analysis confirmed eugenol (68.4%) and β-caryophyllene (12.1%) as major constituents. MRSA infection (K2) provoked a severe inflammatory state (TNF-α: 17.92 ± 0.42 pg/mL; IL-10: 110.21 ± 2.72 pg/mL). The 100 mg extract dose (P3) significantly suppressed TNF-α (7.40 ± 0.48 pg/mL, p<0.001) and normalized IL-10 (49.92 ± 2.56 pg/mL), demonstrating non-inferiority to Vancomycin (p=1.000). Bacterial load was reduced by 4 log units (1.2 × 10³ vs 5.8 × 10⁷ CFU/g). Conclusion: Standardized S. aromaticum extract functions as a potent immunomodulator, resolving MRSA-induced inflammation by balancing pro- and anti-inflammatory cytokines, thereby facilitating the transition from the inflammatory to the proliferative phase of healing.